Review of the Implementation of the Concept of Sustainable Tourism on the Manado Bay - Felly Ferol Warouw; Sonny Davy Mailangkay; Djubir Kembuan; Telly Tangkere; Lady Grace Jane Giroth (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Sustainable development of the Manado Bay travel coast is essential. Tour coast is one of the foundations of sustainable tourism and has significantly aided in development. The standards of environmental sustainability for coastal tourism must be observed if development is to continue holding fast and providing its greatest contribution. must be planned using the accepted standards of sustainable development. Community participation plays a key role in determining if sustainable ecotourism development criteria are met. This study intends to categorise the city of Manado’s coastal tourism patterns from a sustainable tourism development perspective. The research location was carried out on the coast of the Manado bay. Descriptive quantitative research is the methodology employed. According to the study’s findings, there were various types of coast and beach. Manado Bay has a variety of tour types, including tours of the beach, the underwater world, culinary travel, and tourism trading. A draught application for sustainable tourism was identified and applied to four locations in a sequential manner with the help of the public. The findings of the study demonstrate that the tourist area dive, tour trade, tour beaches, and tour culinary are where the public’s opinion of implementation indicators is most concerned. Understand the terms of the proposed tourist sustainability demonstration that is being held along the Manado Bay coast.